POSITIVE EMOTION MEMEDIASI SALES PROMOTION DAN STORE ENVIRONMENT TERHADAP IMPULSE BUYING - Devi, Ni Wayan Cynthia; Jatra, I Made (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p15, 2020)
Impulse buying is the behavior to make purchases directly, without prior plan, done quickly and without much evaluation. Companies need to pay attention to factors that influence the creation of impulse buying to increase revenue. Purpose of this study is to determine Positive Emotion in mediating sales promotion and store environments in impulse buying. Study is conducted in Denpasar and Alfamart as research objects. 112 are used as respondents who had shopped at Alfamart with purposive sampling. Data collected through questionnaires and analyzed using path analysis. Based on the results, sales promotion and store environment have a positive and significant effect on Positive Emotion, Positive Emotion has a positive and significant effect on impulse buying, sales promotion and store environment has a positive and significant effect on impulse buying, and Positive Emotion is able to mediate the influence of sales promotion and store environment for impulse buying. Keywords: sales promotion, store environment, Positive Emotion, impulse buying.